The effectiveness of student clinician communication skill in educating the patients for a shared decision-making / Siti Mariam Ab Ghani... [et al.] - Ab Ghani, Siti Mariam; Kamarulazli, Ariff Ashyraf; Othman, Norlian; Mustaza, Teh Adilla (Universiti Teknologi Mara Cawangan Pulau Pinang, 2017)
Shared decision-making (SDM) is a developing trend in clinical medicine but has by far received little attention in the dental literature. Informative education plays a vital role in SDM by helping patients and clinicians to decide on treatment plan. The objective of the study is to compare patients’ improvement of knowledge by different educational approaches; face-toface educational discussion by student clinicians and non-face-to-face mobile dental applications education (MDAE). Four hundred and fifty participants were segregated into three groups; Group 1: no MDAE or discussion session (n:150), Group 2: discussion session approach (n: 150) and Group 3: MDAE approach (n:150). Quizzes on a mobile dental application (MDA) were used to gauge participants’ knowledge and analyzed using chi square test. No significant differences in subjects’ baseline knowledge, with 55.0% in Group 1, 52.7% in Group 2 and 60.7% in Group 3. However, following different educational approaches, Group 2 (61.3%) had significant increase in knowledge compared to Group 1 (35.0%) and Group 3 (44.0%). A perception survey reported that more than half of Group 2 and Group 3 gave positive feedbacks to the two educational approaches in improving knowledge for SDM. Face-to-face discussion is still the most effective educational approach in promoting SDM compared to non-face-to-face MDAE. This result highlights the effectiveness of student clinicians’ communication skill in educating the patients and improvement required to enhance the usage of MDAE.